Unexplained pulmonary embolism post SARS-CoV2 pneumonia in a patient with MYH9-related disease: a case report - Tomaino, Laura; Menditto, Vincenzo Giannicola; Nitti, Cinzia; Moroncini, Gianluca; Salvi, Aldo (Acta Biomedica Atenei Parmensis, 2021)
This report describes the case of a man affected by Myosin Heavy Chain 9 (MYH9)-related platelet disorder, with a recent history of SARS-CoV-2 pneumonia, who developed pulmonary embolism (PE). At the admittance the patient presented a marked thrombocytopenia. The rotational thromboelastometry (ROTEM) showed a reduction in maximum clot firmness. The CT scan showed a lobar PE while and no sign of superficial or deep venous thrombosis was found. Given the contraindication of anticoagulant therapy due to severe thrombocytopenia, after collegial evaluation of the case, an inferior vena cava filter was applied. The patient was discharged after 5 days of hospitalization, and fondaparinux 2.5 mg subcutaneously was prescribed for two months. Could MYH9 mutation contribute to thrombotic predisposition? Or rather the endothelial dysfunction induced by SARS-CoV-2 infection? The report presents a dissertation on the possible causes for the PE and describes the therapeutic strategy adopted.